Assessment of maternal and fetal outcomes according to induction methods following negative oxytocin challenge test: Negative oxytocin challenge test outcomes - Aytekin, Okan; Erturk Aksakal, Sezin; Altay, Mehmet Metin (Journal of Surgery and Medicine, 2024)
Background/Aim: There is insufficient information about how long fetal well-being will last after a negative oxytocin challenge test (OCT) and the factors affecting this process. We aim to evaluate maternal and perinatal outcomes in high-risk patients who had negative OCTs and to investigate the effects of methods of induction on the development of fetal distress. Methods: The study was designed as a retrospective cohort study. Data of patients who were hospitalized in the perinatal intensive care unit due to high-risk pregnancies between January 2016 and December 2016 were reviewed retrospectively. The patient’s gestational age, gravidity, parity, and body mass index (BMI), risk factors leading to the OCT, labor induction methods used following a negative OCT, time from negative OCT to delivery, mode of delivery, and indications for cesarean section were recorded. In addition, data regarding fetal sex, birth weight, birth height, labor complications, Apgar scores at minutes 1 and 5, admission to the neonatal intensive care unit (NICU), indications for NICU admission, length of NICU stay, and stillbirth were also recorded. Results: OCT was performed on 551 patients and was negative in 447 patients. Among patients with a negative OCT, labor induction was preferred in 427 (95.5%) patients. When fetal distress development was assessed according to the induction method used following a negative OCT, fetal distress developed in 9.1% of 427 patients who underwent labor induction. Conclusion: When outcomes were considered in pregnant women with a negative OCT, it was observed that there were no fetal deaths and a limited number of newborns with low Apgar scores. Further randomized studies are needed to draw definitive conclusions.